2008
DOI: 10.1177/1010539508322251
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation, Integration, and Long-term Commitment: What Solomon Islanders and Development Workers Say About Health Sector Aid

Abstract: Themes and quotations arising from the analyses may assist in understanding theoretical frameworks for coordination, particularly in postconflict states. Future needs regarding mechanisms of collaboration in the Solomons are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Located in the south Pacific about 1,800 kilometres north-east of Australia, the Solomon Islands has a population of 515,870 [5], spread over 9 provinces and 350 populated islands [6,7]. The Solomon Islands is a "least developed country" (LDC) [8], defined by low income, human resource weakness and economic vulnerability, and is ranked 123 of 169 countries on the United Nations Development Program (UNDP) Human Development Index [9].…”
Section: Introductionmentioning
confidence: 99%
“…Located in the south Pacific about 1,800 kilometres north-east of Australia, the Solomon Islands has a population of 515,870 [5], spread over 9 provinces and 350 populated islands [6,7]. The Solomon Islands is a "least developed country" (LDC) [8], defined by low income, human resource weakness and economic vulnerability, and is ranked 123 of 169 countries on the United Nations Development Program (UNDP) Human Development Index [9].…”
Section: Introductionmentioning
confidence: 99%
“…Short‐term projects may have negative consequences if they are not coordinated with local health care and lack adequate follow‐up . Poorly planned aid projects may increase dependence on foreign aid, compete with local resources, decrease local investment in health care, and undermine confidence in local providers . Dickson and Dickson reported that local providers who cannot compete with Western volunteers may become so dissatisfied that they choose to emigrate, further harming the developing country…”
Section: Literature Reviewmentioning
confidence: 99%
“…Effective models for short‐term humanitarian health work include principles that have much in common with general volunteer program guidelines . The Health Volunteers Overseas model contains elements in common with the volunteer management cycle and additional elements specific to humanitarian health work in developing countries .…”
Section: Literature Reviewmentioning
confidence: 99%
“…The country's health system is heavily donor-reliant. Recent health system initiatives include a sector-wide approach to health, which emphasises a Ministry of Health-mandated strengthening of health sector management and greater co-ordination of health services with the national health plan [10-12]. However, the health system has to date failed to meet many identified health targets [13].…”
Section: Introductionmentioning
confidence: 99%